A promising research direction for colorectal cancer immunotherapy: The regulatory mechanism of CCL5 in colorectal cancer - Li, Yuansen; Lei, Yi; Sun, Jiaxue; Zhang, Wanfu; Li, Xiaogang; Chen, Sijing; Kong, Deshenyue; Chen, Cheng; Bi, Ke; Luo, Xiao; Wang, Hui; Li, Bo; et al. (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the leading causes of cancer death worldwide, with high morbidity and mortality rates worldwide. Therefore, there is an urgent need to develop more and more effective treatments for CRC patients. In recent years, there has been some success in immunotherapy of tumors, and immunotherapy has been used in many solid tumors including CRC. To date, the clinical efficacy of immunotherapy for CRC is limited, so more effective immunotherapy methods need to be explored. In patients with CRC, the CC chemokine CCL5 plays a role in the development of CRC and the recruitment and activation of immune cells, suggesting that it has the potential for immunotherapy. This review mainly introduces the latest advances in the study of CCL5 as a marker of CRC and related mechanisms of immunotherapy, as well as the latest understanding of how CCL5 is involved in the invasion and development of CRC.